Micro and macro policies in the Keynes+Schumpeter evolutionary models - Giovanni Dosi; Mauro Napoletano; Andrea Roventini; Tania Treibich (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2014)
This paper presents the family of the Keynes+Schumpeter (K+S, cf. Dosi et al, 2010, 2013, 2014) evolutionary agent-based models, which study the effects of a rich ensemble of innovation, industrial dynamics and macroeconomic policies on the long-term growth and short-run fluctuations of the economy. The K+S models embed the Schumpeterian growth paradigm into a complex system of imperfect coordination among heterogeneous interacting firms and banks, where Keynesian (demand-related) and Minskian (credit cycle) elements feed back into the meso and macro dynamics. The model is able to endogenously generate long-run growth together with business cycles and major crises. Moreover, it reproduces a long list of macroeconomic and microeconomic stylized facts. Here, we discuss a series of experiments on the role of policies affecting i) innovation, ii) industry dynamics, iii) demand and iv) income distribution. Our results suggest the presence of strong complementarities between Schumpeterian (technological) and Keynesian (demand-related) policies in ensuring that the economic system follows a path of sustained stable growth and employment.
Keywords: C63; E32; E6; E52; G01; G21; O4; 330; agent-based model; fiscal policy; economic crises; austerity policies; disequilibrium dynamics